Voluntary food intake, live-weight change and lactation performance of crossbred dairy cows given ad libitum Pennisetum purpureum (napier grass var. Bana) supplemented with leucaena forage in the lowland semi-humid tropics - Muinga, R.W.; Thorpe, W.R.; Topps, J.H. (Cambridge University Press, 1992)
Details the voluntary food intake, live-weight change and lactation performance of 36 crossbred Ayrshire/Brown Swiss X Sahiwal cows fed from the 3rd week of lactation for 14 weeks on diets of napier fodder offered ad libitum and supplemented w. fresh leucaena fodder. Average daily milk yield during the 2nd week of lactation was a covariate in the analyses of milk yield, and post-partum live weight a covariate in the analyses of dry matter (DM) intake and live-weight change. The results show that good dairy performance can be achieved in the tropics by supplementing a napier fodder basal diet w. leucaena forage, and highlights the importance of the stage of harvesting of the forage. Results are discussed in relation to the nutrient requirements for milk production given by the Agricultural Research Council (1980 and 1984).